Haptic Feedback to Support the Conceptualization of the Shape of Virtual Objects: An Exploratory Study - Ceccacci, S.; Gentilozzi, C.; Marfoglia, A.; Santilli, T.; Mengoni, M.; Capellini, S. A. [UNESP]; Giaconi, C. (Springer Nature, 2023)
Virtual museum systems have been shown to play a key role in enhancing visitor’s experience and increasing the accessibility of cultural artifacts. In this context, the use of haptic interfaces based on force feedback could increase the level of immersivity of these systems and the quality of the interaction between visitors and cultural artifacts, introducing tactile information that could enrich the experience of all people, also in the case of visitors with disability. However, HD present limits concerning the ease of use of the device. This paper provides the results of an exploratory research carried out within the Research center of Teaching and learning, Disability and Educational Technology of the University of Macerata (TIncTec), consisting in two studies. Study 1 aims to analyze the learning performance of people with and without disabilities concerning this device. Study 2 aims to assess whether HD can provide useful support for conceptualizing the shape of virtual objects. To this end, we considered the 6 DoF high fidelity force feedback Geomagic Touch X by 3D system. A total of 30 people has been involved, including both children and adults with and without disabilities. The considered VR applications were developed in Unity 3D, using the 3D Systems Openhaptics Unity Plugin. The results provide useful insights for the design of future HD-based applications, showing how haptic technology can properly support visitors with disability in virtual museum environments in an inclusive perspective.
Keywords: Accessibility; Cultural Heritage; Force Feedback; Haptic Interfaces; Inclusive Museum; Special Education; Virtual Museum; XR Technologies